SISTEM INFORMASI PENJUALAN PERLENGKAPAN BAYI DENGAN MENGGUNAKAN METODE DISTRIBUSI LANGSUNG PADA JONNY SHOP - Robert; Abdullah; Sudirman (KHARISMA Tech, 2021)
This study aims to design a system to manage the sale of baby supplies at the Shop Jonny Shop. To obtain data and information of researcher do observation and interview. Information Systems Stock control is designed using Data Flow Diagrams (DFD), then implemented using Visual Basic 6.0 and Microsoft Access programming as a data processor, then tested using black box testing method. With the new system is expected owner and manager Jonny Shop can manage the sale of baby supplies.